2011
DOI: 10.1152/jn.00016.2011
|View full text |Cite
|
Sign up to set email alerts
|

Representation of comparison signals in cortical area MT during a delayed direction discrimination task

Abstract: Lui LL, Pasternak T. Representation of comparison signals in cortical area MT during a delayed direction discrimination task. J Neurophysiol 106: 1260 -1273, 2011. First published June 15, 2011 doi:10.1152/jn.00016.2011.-Visually guided behavior often involves decisions that are based on evaluating stimuli in the context of those observed previously. Such decisions are made by monkeys comparing two consecutive stimuli, sample and test, moving in the same or opposite directions. We examined whether responses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 35 publications
6
54
0
Order By: Relevance
“…MT neurons can show a direction-selective response to coherent motion far outside of the classic RF-even when the motion is located in the ipsilateral hemifield (Zaksas and Pasternak 2005). It is thought that this information arrives in MT through feedback connections, likely from prefrontal cortex (Hussar and Pasternak 2010;Lui and Pasternak 2011;Zaksas and Pasternak 2006). The same mechanism could explain why LFP power was correlated with the subject's detection performance when there was no coherent motion pulse in the RF.…”
Section: Discussionmentioning
confidence: 99%
“…MT neurons can show a direction-selective response to coherent motion far outside of the classic RF-even when the motion is located in the ipsilateral hemifield (Zaksas and Pasternak 2005). It is thought that this information arrives in MT through feedback connections, likely from prefrontal cortex (Hussar and Pasternak 2010;Lui and Pasternak 2011;Zaksas and Pasternak 2006). The same mechanism could explain why LFP power was correlated with the subject's detection performance when there was no coherent motion pulse in the RF.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, however, sustained and content-specific patterns of spiking persist in lPFC, and this persistent spiking in PFC may provide important top-down feedback to MT that induces a locally spike-silent but content-specific change in LFPs (Figure 8). Finally, under this coding scheme, the presentation of a matching test stimulus at the end of the delay period may more easily trigger the re-emergence of the same spiking pattern that was present in MT during the encoding of the sample stimulus, as this pattern is held in a ‘primed’ state during the STM delay period via the continuous top-down modulation of LFPs (see also: Lui & Pasternak, 2011 for conceptually related ideas). Importantly, because this tonic top-down input to MT is generated via sustained spiking activity in distal lPFC, the content-specific patterns of sub-threshold membrane potentials in MT could co-exist with and persevere through bouts of local spiking in MT that are evoked by other distracting stimuli presented during the delay period.…”
Section: Alternate Mechanisms Of Storage – Dynamic and Activity (Spikmentioning
confidence: 99%
“…Two reciprocally interconnected cortical regions relevant to these tasks are motion-processing area MT and the dorsolateral region of the prefrontal cortex (PFC) associated with sensory maintenance and executive control (Barbas, 1988; Miller and Cohen, 2001; Petrides and Pandya, 2006). Our recent work showed that MT neurons, in addition to exhibiting direction selective (DS) responses to motion, carried some stimulus-related activity during the delay and their responses during the comparison phase of the task reflected the previously presented direction (Zaksas and Pasternak, 2006; Lui and Pasternak, 2011). …”
Section: Introductionmentioning
confidence: 99%